Jewellery in the age of modernism 1918-1940 : adornment and beyond - Bliss, Simon (Material Culture of Art and Design Ser., 2019)
"Why has jewellery and body adornment often been marginalized in studies of modernist art and design? This study explores the relationship between jewellery, modernism and modernity from the 'jazz age' to the second world war in order to challenge the view that these portable art forms have only a minor role to play in histories of modernism. From the masterworks of the Parisian jewellery houses to the film and photography of Man Ray, this study seeks to present jewellery in a new light, where issues of representation and display are considered to be as important in the creation of a modern 'jewellery culture' as the objects themselves. Drawing on material from museums, archives, contemporary journals, memoirs, literary and theoretical texts, this study shows how the emergence of modern jewellery began to seriously question conventional notions of body adornment."--Bloomsbury Publishing.